Initial Study of Column-Integrated Aerosol Optical Properties over Birkat al Mouz, Sultanate of Oman - Baiju Dayanandan; Nirmal Krishna; Ajay Parottil; Vinoj Velu; Ahmed Al Harrasi; Binisia Sanatan; Pawan Gupta; Tom Eck; Alexander Smirnov; Humaid AlBadi (Aerosol and Air Quality Research)
Abstract Purpose This study aims to provide the first analysis of aerosol optical properties, radiative forcing, and source identification over Birkat al Mouz, Oman, using Aerosol Robotic Network (AERONET) data from December 2022 to November 2024. Methods We analyzed Aerosol Optical Depth (AOD), Angstrom Exponent (AE), Single Scattering Albedo (SSA), aerosol radiative forcing (RF), and performed Concentration-Weighted Trajectory (CWT) analysis to identify aerosol transport pathways and sources. Results The highest aerosol loading (AOD = 0.49 ± 0.15) occurred in summer, with the lowest (0.17 ± 0.08) in winter. AE values (maximum 0.94 ± 0.20 in winter, minimum 0.42 ± 0.17 in summer) indicated coarse-mode aerosol dominance. Seasonal SSA values were highest in summer (0.95), confirming significant dust aerosol influence. Surface RF averaged − 43.81 W m−2, atmospheric RF was 27.04 W m−2, and aerosol-induced heating reached 0.74 K day−1. CWT analysis revealed the Horn of Africa, and arid regions of the Arabian Peninsula as major aerosol sources. Conclusion Seasonal aerosol variations in Birkat al Mouz are predominantly driven by dust aerosols transported from remote regions, highlighting their significant role in regional climate forcing. Graphical abstract